Factors influencing the prevalence of anaemia in teenage girls in the workplace of Abiansemal III Community Health Center, Bali - Luh Putu Widiastini; I Gusti Agung Manik Karuniadi (Gema Lingkungan Kesehatan, 2025)
Anemia is a global health problem that has a serious impact, especially on children, adolescent girls, menstruating women, and pregnant and postpartum women. Approximately 30% of women aged 15-49 years in the world experience anemia. Efforts to prevent anemia are focused on vulnerable groups, including adolescent girls, one of which is through the provision of Blood Addition Tablets, although its implementation still faces various obstacles. In addition, other factors such as lack of knowledge, attitudes, and poor menstrual patterns also contribute to the high incidence of anemia. The purpose of this study was to analyze the factors that influence the incidence of anemia in adolescent girls. A quantitative research methodology with a cross-sectional approach was used. The sample selection technique was non-probability sampling, namely, purposive sampling. A total of 85 adolescent girls who attended adolescent posyandu were selected as the samples. The young women completed a questionnaire and had their hemoglobin levels measured. Spearman’s rho test and logistic regression were used for the analysis. Based on the results of Spearman’s rho analysis, 12 respondents were anemic, 9 respondents had a fair attitude, and 3 respondents had a good attitude. Logistic regression analysis showed that attitude was the dominant variable (p = 0.000). Based on the OR value obtained of 18.492, then the poor attitude of adolescent girls has an 18.492 times greater chance of causing anemia in adolescent girls